ANALISIS TEKSTUR KULIT SAPI BERDASARKAN EKSTRAKSI CIRI CITRA - Nunik Purwaningsih; Jamila Jamila (Politeknik ATK Yogyakarta, 2016)
One of the animals whose leather is often taken and used in the leather industry is cow. There is cow leather having its original texture and some has been printed with other animal’s texture, meaning not in its original texture. Visually, it is difficult to know whether or not the cow leather printed with other motifs still have features of its original texture. This research aims to analyze the features of original cow leather texture and of that which has been modified. The research is conducted by feature extraction of the leather image using Gray Level Cooccurrence Matrix (GLCM). There are five features calculated including contrast, correlation, energy, entropy, and homogeneity. The experiments proved that the four angles of GLCM show the same thing, i.e. for contrast and entropy, the images of the cow leather that has been modified have higher value than those of original texture. While for the correlation, energy, and homogeneity the images of the cow leather that has been modified have a lower value than those taken from leather with its original texture.